2013
DOI: 10.1177/0266666912467449
|View full text |Cite
|
Sign up to set email alerts
|

User acceptance of Internet banking in Indonesia: initial trust formation

Abstract: Most research on Internet banking adoption has focused on a limited set of determinants that influence users' initial trust. This study takes the uncommon approach of separating the constructs of trust, perceived security, and perceived privacy to reveal the impact that each of these distinct factors has on initial trust formation. A large-scale survey of prospective Internet banking service customers in Indonesia was conducted and the results analyzed using a structural equation modeling approach. Perceived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 71 publications
4
38
0
1
Order By: Relevance
“…It is clearly show that assessing trust to user acceptance and IS success constructs are connected within a sequential influence context. It is consistent with indications of the previous study which indicated that adaptation of the prior models in the social studies is a common model development, in regard to explore the new model [25,[29][30][31].…”
Section: Intsupporting
confidence: 91%
See 1 more Smart Citation
“…It is clearly show that assessing trust to user acceptance and IS success constructs are connected within a sequential influence context. It is consistent with indications of the previous study which indicated that adaptation of the prior models in the social studies is a common model development, in regard to explore the new model [25,[29][30][31].…”
Section: Intsupporting
confidence: 91%
“…According the DeLone and McLean's [16] that IS success model also use the process and output dimensions of the IPO logic. In term of the transaction, the author believed that the trust factor is also one of the input factors [30,31].…”
Section: Research and Discussionmentioning
confidence: 99%
“…Perceived privacy (Al-Sharafi et al, 2016;Colesca, 2009;Gupta and Dhami, 2015;Lean et al, 2009;Mayeh et al, 2013;Ramos et al, 2018;Ranaweera, 2016;Susanto et al, 2013) Perceived security (Al-Sharafi et al, 2016;Ponte et al, 2015;Gupta and Dhami, 2015;Mayeh et al, 2013;Normalini and Ramayah, 2017;Ramos et al, 2018;Ranaweera, 2016;Susanto et al, 2013) Social media characteristics Structural assurances (Gefen et al, 2003;Kim et al, 2009;Kim and Prabhakar, 2004;Oliveira et al, 2014;Xin et al, 2015) Information quality (Abu-Shanab, 2014;Ayyash et al, 2013;Ponte et al, 2015;Nicolaou and McKnight, 2006;Ranaweera, 2016;Wang, 2017;Weerakkody et al, 2016) Perceived ease of use (Al-Sharafi et al, 2017;Alsaghier and Hussain, 2012;Ayyash et al, 2013;Belanche et al, 2012;Gefen et al, 2003;Ramos et al, 2018) Perceived usefulness (Alsaghier and Hussain, 2012;Ayyash et al, 2013) A model has been proposed to provide a holistic view on the antecedents of citizens' trust in using social media for e-government services as illustrated in Fig 4. The model also reflects the influence of trust towards citizens' intention to use social media for egovernment services. Antecedents of trust in Fig 4 represent the group of factors that can influence citizens' trust in using ...…”
Section: Resultsmentioning
confidence: 99%
“…The banking industry is one of the frontrunners when it comes to capitalising on the opportunities provided by the Internet due to the implementation of Internet banking (Martins, Oliveira & Popovič, 2014;Wang & RubensteinMontano, 2003). Internet banking has the potential to be one of the most profitable financial services (Lee, 2009;Susanto, Lee, Zo & Ciganek, 2013). However, the acceptance rate of Internet banking is not as widespread as initially predicted (Lichtenstein & Williamson, 2006;Maduku, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the acceptance rate of Internet banking is not as widespread as initially predicted (Lichtenstein & Williamson, 2006;Maduku, 2014). Low levels of customer trust are widely cited as one of the common barriers to the rapid acceptance of Internet banking (Kim, Ferrin & Rao, 2009;Susanto et al, 2013;Yousafzai, Foxall & Pallister, 2010). This is because, although all transactions call for some degree of trust, those that are carried out within the uncertain and impersonal circumstances of the Internet require substantial levels of trust owing to the high level of risk commonly associated with online transactions (McKnight, Choudhury & Kacmar, 2002).…”
Section: Introductionmentioning
confidence: 99%